2018
DOI: 10.18203/2349-2902.isj20183718
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparative study between laparoscopic and open appendectomy in teaching hospital of India

Abstract: Background: This study was aimed to compare laparoscopic with open appendicectomy and ascertain the therapeutic benefit, in the overall management of appendicitis. Laparoscopic appendicectomy though widely practiced has not gained universal approval. Laparoscopic appendicectomy in India is relatively new and the literature is exiguous.Methods: The study group consisted of 100 patients suffering from appendicitis. 40 patients underwent laparoscopic appendicectomy (LA) and 60 patients underwent open appendececto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Both laparoscopic appendectomy and open appendectomy are commonly prac sed in ter ary 1 care centres. The outcome in terms of dura on of surgery, length of hospital stay, pain, wound infec on reported by various [2][3][4][5][6] studies in different se ngs was different. We found the mean age of the open appendectomy group was 30±16.85 years and the laparoscopic appendectomy group was 33.47 ±13.29 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both laparoscopic appendectomy and open appendectomy are commonly prac sed in ter ary 1 care centres. The outcome in terms of dura on of surgery, length of hospital stay, pain, wound infec on reported by various [2][3][4][5][6] studies in different se ngs was different. We found the mean age of the open appendectomy group was 30±16.85 years and the laparoscopic appendectomy group was 33.47 ±13.29 years.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of appendectomy ma ers whether it is an open appendectomy or laparoscopic appendectomy. The outcome in terms of dura on of surgery, length of hospital stay, pain, and wound infec on reported by various studies [2][3][4][5][6] in different se ngs was different. A study found the postopera ve pain and hospital stay were less in 2 laparoscopic appendectomy than open appendectomy.…”
Section: Laparoscopic Appendectomy Is a New Technique Than Open Appen...mentioning
confidence: 99%